2012
DOI: 10.1210/jc.2011-1858
|View full text |Cite
|
Sign up to set email alerts
|

Altered Plasma Adipokine Levels andin VitroAdipocyte Differentiation in Pediatric Type 1 Diabetes

Abstract: The adipogenic effects of diabetic plasma in vitro and the altered adipokine levels in vivo suggest adipose tissue involvement in the low-grade inflammation associated with T1D, already in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 40 publications
3
29
1
2
Order By: Relevance
“…Verrijn Stuart et al found that hyperglycaemic plasma from type 1 diabetes patients enhanced the extent of adipocyte differentiation of normal preadipocytes [24]. However, high glucose concentrations alone had no effect of adipogenesis.…”
Section: High Glucose Levels and Adipocyte Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…Verrijn Stuart et al found that hyperglycaemic plasma from type 1 diabetes patients enhanced the extent of adipocyte differentiation of normal preadipocytes [24]. However, high glucose concentrations alone had no effect of adipogenesis.…”
Section: High Glucose Levels and Adipocyte Differentiationmentioning
confidence: 99%
“…Verrijn Stuart et al found that in type 1 diabetes patients, plasma levels of adiponectin, leptin, retinal binding protein (RBP)-4, cathepsin S, tissue inhibitor of metalloproteinase-1, chemerin, serum amyloid A-1, plasminogen activator inhibitor-1 (PAI)-1, and CCL2 levels were increased compared to control subjects [24]. No significant differences were found in the other plasma adipokines studied, including IL-1RA, IL-1β, IL-6, IL-10, TNF-α, interferon-γ, macrophage inhibitory factor, IL-8, C-X-C motif ligand (CXCL) 10, γ interferon inducible protein 10, granulocyte-macrophage colony stimulating factor, resistin, thrombopoietin, and adipsin.…”
Section: High Glucose Levels Inflammation and Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Badania nad rolą tej adipocytokiny w patogenezie cukrzycy typu 1 i jej powikłań naczyniowych nie są liczne [12][13][14]. Czy poprzez zaangażowanie tkanki tłuszczowej w patomechanizm obu schorzeń cukrzyca typu 1 i 2 może stanowić swego rodzaju kontinuum?…”
Section: Wstępunclassified
“…Stężenie IFN-γ u pacjentów z cukrzycą typu 1 i w grupie kontrolnej Fig. 3 żenie chemeryny jest istotnie większe zarówno w cukrzycy nowo rozpoznanej, jak i trwającej powyżej roku w porównaniu z grupą kontrolną [12]. Grupa holenderska obejmowała jednak zaledwie dwadzieścioro dzieci z nowo rozpoznaną oraz dwadzieścioro dzieci z dłużej trwającą cukrzycą [12].…”
Section: Dyskusjaunclassified